2020
DOI: 10.1088/1361-6560/ab79c5
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning-based real-time tumor tracking system for fluoroscopic gating of lung radiotherapy

Abstract: To improve respiratory-gated radiotherapy accuracy, we developed a machine learning approach for markerless tumor tracking and evaluated it using lung cancer patient data. Digitally reconstructed radiography (DRR) datasets were generated using planning 4DCT data. Tumor positions were selected on respective DRR images to place the GTV center of gravity in the center of each DRR. DRR subimages around the tumor regions were cropped so that the subimage size was defined by tumor size. Training data were then class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…To date, several studies have demonstrated the potential to eliminate the use of markers altogether through markerless tracking 35–37,50–55,57,59–64 . The implementation of markerless tracking is considered the ideal technique for the patient and the healthcare system due to its non‐invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have demonstrated the potential to eliminate the use of markers altogether through markerless tracking 35–37,50–55,57,59–64 . The implementation of markerless tracking is considered the ideal technique for the patient and the healthcare system due to its non‐invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The system achieved an accuracy of <0.5 mm when tested on a moving chest phantom 54 . When tested on images from eight patients, the mean (±SD) tumour position error was 1.0 ± 0.3 mm in 3D space based on paired X‐ray images 55 . Furthermore, the ML algorithm was shown to be accurate when trained with DRRs generated from a simulated 4DCT 57 …”
Section: Markerless‐based Approachesmentioning
confidence: 96%
See 1 more Smart Citation
“…The markerless tracking algorithm uses a machine learning approach. The model parameters is required for every patient using 4DCT for respective patients [7,8].…”
Section: Markerless Tracking Accuracymentioning
confidence: 99%
“…At that time, this markerless tracking technique used fluoroscopic image registration and machine learning approaches; however, it required preparation of reference data before irradiation. To solve this problem, we used a machine learning approach with treatment planning 4DCT for each patient and used it on the fluoroscopic image data acquired during irradiation to track the tumor position [7][8][9]. As we know, there is no markerless tracking algorithm with a single machine learning model file that can be applied to every patient; therefore, treatment planning 4DCT for each patient was required.…”
Section: Introductionmentioning
confidence: 99%